Simulation-Based Origin-Destination Matrix Reduction: A Case Study of Helsinki City Area - Klavdiya Bochenina; Anton Taleiko; Laura Ruotsalainen (SUMO Conference Proceedings, 2023)
Estimation of a travel demand in a form of origin-destination (OD) matrix is a necessary step in a city-scale simulation of the vehicular mobility. However, an input data on travel demand in OD matrix may be available only for a specific set of traffic assignment zones (TAZs). Thus, there appears a need to infer OD matrix for a region of interest (we call it ‘core’ area) given OD matrix for a larger region (we call it ‘extended’ area), which is challenging as trip counts are only given for zones of the initial region. To perform a reduction, we explicitly simulate vehicle trajectories for the extended area and supplement trip values in ‘core’ TAZs based on the recorded trajectories on the border of core and extended areas. To keep validation results consistent between extended and core simulations, we introduce edge-based origin-destination assignment algorithm which preserves properties of traffic flows on the border of the core area but also keeps randomness in instantiating simulation for the core area.